Spatial Analysis of GHG Balances and Climate Change Mitigation in Rural Areas: The Case of Emilia–Romagna Region - Katia Federico; Alberto Bonora; Gianmarco Di Giustino; Matelda Reho; Giulia Lucertini (Atmosphere, 2022)
This paper aims to analyse the issue of mitigation and the balance of greenhouse gases in the rural contexts of the Emilia–Romagna region (Italy) due to climate change. The approach is based on the experimentation of a methodology, populated by available spatial databases and refined with a series of technical meetings, where it was possible to weigh availability and alternative choices within the identified assessment model. The objective of the research is to create a regional GHG balance map, in order to classify the territory for this specific dynamic. The aim of this approach is supporting policy decisions related to the Common Agricultural Policy at a regional level.